Policy and institutional study on the strategic role of water storage in Bangladesh - de Silva, Sanjiv; Jirasinha, Radheeka; Mondal, M. S.; McCartney, Matthew P. (International Water Management Institute, 2024)
This policy and institutional study was conducted as part of the Built Water Storage in South Asia (BWSSA) project (2023–2026), implemented by the International Water Management Institute (IWMI) and the Global Water Partnership (GWP). The BWSSA initiative aimed to transform how water storage—both built (gray) and natural (green) infrastructure—was perceived, planned, and managed across five countries: Nepal, India, Bhutan, Bangladesh, and Pakistan. The project sought to strengthen national capacity for integrated storage planning, promote data-informed decision-making, support regional dialogue, and address inequities in access and benefit-sharing related to water storage.